Method Evaluation for Chemical Oxygen Demand (COD) in Wastewater Treatment Plant Samples from an Industrial Estate using Closed Reflux Colorimetry - Junjunan Muhammad Syukur; Erna Styani; Muhammad Yanwar Prasetyo (Jurnal Kimia Sains dan Aplikasi, 2026)
This study presents the verification of the APHA Standard Method 5220 D for determining chemical oxygen demand (COD) in wastewater using a spectroscopic closed-reflux colorimetric system. Both the low range (LR: 0–90 mg O2/L) and high range (HR: 90–700 mg O2/L) methods were verified to ensure their suitability for wastewater monitoring in the industrial estate, with the LR method applied to effluent samples and the HR method applied to influent samples. Method performance was evaluated using linearity, sensitivity, limit of detection (LOD), limit of quantification (LOQ), limit of linearity (LOL), precision, accuracy, and measurement uncertainty for both LR and HR COD levels. The calibration curves exhibited excellent linearity, with coefficients of determination (R2) of 0.9991 (LR) and 0.9996 (HR). The LOD (3Syx/b) and LOQ (10Syx/b) values were 3.34 and 11.14 mg O2/L for LR, and 15.48 and 51.59 mg O2/L for HR, respectively. Precision testing produced %RSD values of 2.88% (LR) and 1.37% (HR), both meeting acceptance criteria based on ⅔ CV Horwitz. Accuracy evaluation using potassium hydrogen phthalate (KHP) standards yielded recoveries of 97.50–106.02% (LR) and 98.83–102.92% (HR), consistent with Association of Official Analytical Chemists (AOAC) requirements. Measurement uncertainty was assessed by combining contributions from calibration, precision, accuracy, and instrumental factors, resulting in expanded uncertainties of ±3.83 mg O2/L for LR and ±13.87 mg O2/L for HR (k = 2). The findings confirm that the method is reliable and suitable for routine COD analysis in wastewater monitoring.